Reducing Network Energy Consumption using Multidimensional Optimization of LEACH Protocol - et. al., Dr.M.Buvana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The optimized LEACH-focused protocol is proposed to make equal network energy usage and outspread the life cycle. In the first place, the threshold function of the cluster head is adjusted and the technique of division of the network area is configured to change reasonably the size of the clusters, taking account of residual energy and node distance. A sleep mechanism is introduced for intra-cluster transmission to balance the power consumption of nodes. And a new Barycenter Node has been introduced to help the head of the cluster fulfill the transmission task and thus prolong the lifespan. We derived a new formula, considering the angle, energy and distance, in multiple-hop communication between clusters to determine the fitting factor of the next hop. The results of simulations display that the remaining total energy of the optimized LEACH is decreased by 32.6% and the network life cycle respectively increases by around 54%.